การพัฒนาโมเลกุลฟลูออเรสเซนซ์คีโมเซ็นเซอร์จากปฏิกิริยาปิดวงของสารบีตาอะมิโนอะคริเลต - ลำดวน จรสาย (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Copper(II) is an important element in the human body. However, its excess from normal permissible limit can induce harmful effects to organ systems such as nervous system that lead to serious diseases, including Alzheimer’s, Parkinson’s and Wilson’s diseases. Herein, novel of dihydrobenzoquinoline (DHBQ) derivative was synthesized from the cyclization reaction of β-aminoacrylates between 3-aminophenol and methyl propiolate in 91 % yield. Its structure was characterized by ¹H NMR, ¹³C NMR, COSY, HMBC, HSQC and maldi-TOF MS spectrometry. The photophysical properties of DHBQ were investigated by UV-visible and fluorescence spectroscopy in which the absorption and emission maximum wavelengths Determined in 10 % H₂O/DMSO were 345 nm and 553 nm, respectively. According to the metal ion sensing results, DHBQ was found to be highly selective to Copper(II) without any other metal ion interferences. In addition, the detection limit of DHBQ was determined as 0.8 μM for copper(II) which was lower than the allowed value of copper(II) ions in drinking water (20 μM) Environmental Protection Agency (EPA).